To determine whether the given points are solutions to the system of equations \( y = 2x + 2 \) and \( y = 2x - 4 \), we can substitute the x-coordinates of each point into both equations.
-
For the point \( (0, -4) \):
- Substitute \( x = 0 \) into the first equation: \[ y = 2(0) + 2 = 2 \] This does not equal \(-4\), so \( (0, -4) \) is not a solution to the first equation.
- Substitute \( x = 0 \) into the second equation: \[ y = 2(0) - 4 = -4 \] This matches the y-coordinate \(-4\), so \( (0, -4) \) is a solution to the second equation.
-
For the point \( (0, 2) \):
- Substitute \( x = 0 \) into the first equation: \[ y = 2(0) + 2 = 2 \] This matches the y-coordinate \(2\), so \( (0, 2) \) is a solution to the first equation.
- Substitute \( x = 0 \) into the second equation: \[ y = 2(0) - 4 = -4 \] This does not equal \(2\), so \( (0, 2) \) is not a solution to the second equation.
Summary:
- The point \( (0, -4) \) is a solution to only the second equation.
- The point \( (0, 2) \) is a solution to only the first equation.
Therefore, the correct response is: Neither of these points are solutions.